High-resolution modeling of early contrail evolution from hydrogen-powered aircraft - A. Lottermoser; S. Unterstrasser (Atmospheric Chemistry and Physics)
In this study, we investigate the properties of young contrails formed behind hydrogen-powered aircraft, particularly compared to contrails from conventional kerosene combustion. High-resolution simulations of individual contrails are performed using the EULAG-LCM model, a large-eddy simulation model with fully coupled particle-based ice microphysics.